2019
DOI: 10.1021/acsomega.8b03447
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Substrate and Inhibitor Selectivity among Human GLUT Transporters through Comparative Modeling and Molecular Docking

Abstract: The solute carrier 2 family is composed of 14 transporters, which are members of the major facilitator superfamily. Despite their high physiological importance, there are still many open questions concerning their function and specificity, and in some cases, their physiological substrate is still unknown. To understand the determinants of the substrate and inhibitor specificity, we modeled all human glucose transport carriers (GLUTs) and simulated their interaction with known ligands. Comparative modeling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The carbonyl, amide, and carboxyl groups on anthraquinone formed hydrogen bonds with amino acid residues respectively, with bond lengths of 3.4, 2.2, 2.0, 2.1, 2.6, and 1.9 Å. The docking sites were essentially the same as those reported in the literature (Ferreira et al, 2019), indicating that the compound NAY could work well with GLUT9, which was consistent with the previous pharmacological activities. Figure 14D shows that the binding energy of NAY and OAT1 is -8.48 kcal/mol.…”
Section: Molecular Docking Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The carbonyl, amide, and carboxyl groups on anthraquinone formed hydrogen bonds with amino acid residues respectively, with bond lengths of 3.4, 2.2, 2.0, 2.1, 2.6, and 1.9 Å. The docking sites were essentially the same as those reported in the literature (Ferreira et al, 2019), indicating that the compound NAY could work well with GLUT9, which was consistent with the previous pharmacological activities. Figure 14D shows that the binding energy of NAY and OAT1 is -8.48 kcal/mol.…”
Section: Molecular Docking Resultssupporting
confidence: 85%
“…uk/) (Jumper et al, 2021;Varadi et al, 2022). The active site of XOD was determined using its original ligand febuxostat, and the active sites of Glut9, OAT1, and OAT3 were determined according to the methods described in the literature (Ferreira et al, 2019;Li et al, 2020). The software Autodock 4.0 was used to carry out molecular docking, according to the method reported in the literature (Steinberger et al, 2000), and then plotted using Pymol software (van Pouderoyen et al, 2001).…”
Section: Molecular Docking Of Naymentioning
confidence: 99%
“…Although WU-1 is a non-competitive inhibitor of PfHT in terms of zero-trans influx (Fig 6), it remains possible that WU-1 is a competitive inhibitor for zero-trans efflux as has been shown for cytochalasin B (CB) [33] and for the HIV protease inhibitor indinavir [31]. Similar to all GLUTs that are inhibited by CB, residues Q282, W388, N411, and W412 (GLUT1 nomenclature) are found in PfHT [34]. When the endofacial ligand CB was used to inhibit glucose uptake in both cell lines, like WU-1, we found that CB was significantly less potent (right-shifted) in inhibiting FTPfHT than PfHT (IC 50 = 29.9 ± 1.8 μM vs 10.9 ± 0.9 μM, p< 0.05, Fig 9B).…”
Section: Resultsmentioning
confidence: 99%
“…The PDSM2 gene encodes a component of the 26S proteasome, a multiprotein complex involved in the ATP-dependent degradation of ubiquitinated proteins [56]. These two proteins have recently attracted attention for their druggable and therapeutic potential [57,58].…”
Section: Discussionmentioning
confidence: 99%